Nicotine Modulates Multiple Regions in the Limbic Stress Network Regulating Activation of Hypophysiotrophic Neurons in Hypothalamic Paraventricular Nucleus - Yu, Guoliang (2012)
Nicotine intake affects CNS responses to stressors. We reported that nicotine self-administration (SA) augmented the hypothalamo-pituitary-adrenal (HPA) stress response, in part due to altered neurotransmission and neuropeptide expression within hypothalamic paraventricular nucleus (PVN). Limbic-PVN interactions involving medial prefrontal cortex, amygdala, bed nucleus of the stria terminalis (BST) greatly impact the HPA stress response. Therefore, we investigated the effects of nicotine SA on stress-induced neuronal activation in limbic-PVN network, using c-Fos protein immunohistochemistry and retrograde tracing. Nicotine decreased stress-induced c-Fos in prelimbic cortex (PrL), anteroventral BST (avBST), and peri-PVN; but increased c-Fos induction in medial amygdala (MeA), locus coeruleus, and PVN. Fluoro-gold (FG) was injected into avBST or PVN, since GABAergic neurons in avBST projecting to PVN corticotrophin-releasing factor (CRF) neurons relay information from both PrL glutamatergic and MeA GABAergic neurons. The stress-induced c-Fos expression in retrograde-labeled FG(+) neurons was decreased in PrL by nicotine, but increased in MeA, and also reduced in avBST. Therefore, within limbic-PVN network, nicotine SA exerts selective regional effects on neuronal activation by stress. These findings expand the mechanistic framework by demonstrating altered limbic-BST-PVN interactions underlying the disinhibition of PVN CRF neurons, an essential component of the amplified HPA response to stress by nicotine.